The Slanting of Subjective Probabilities–Agreement on Some Essentials - Brewer, K. R. W.; Fellner, William (Quarterly Journal of Economics, 1965)
K. R. W. Brewer, William Fellner; The Slanting of Subjective Probabilities — Agreement on Some Essentials, The Quarterly Journal of Economics, Volume 79, I